Design and Validity of Interactive Multimedia Based on Cognitive Conflict on Static Fluid Using Adobe Animate CC 2019 - Muhammad Dhanil; Fatni Mufit (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This study aims to produce valid cognitive conflict-based interactive multimedia. This study uses the Plomp development model, which reports the results of the preliminary study and the prototyping phase. In the preliminary phase, five journals were analyzed and data were collected through teacher questionnaires. In the prototyping phase, multimedia is designed and self-evaluation is carried out and data collection is carried out through expert review questionnaires. The results of the journal analysis show that students' misconceptions about static fluid material are quite high. The results of the questionnaire show that learning is still teacher-centered, and interactive multimedia teaching materials are not yet available that can improve understanding of 4C concepts and skills. Based on the results of the preliminary research, in the prototyping phase, interactive multimedia based on cognitive conflict was designed using the Adobe Animate CC 2019 application. Interactive multimedia was arranged according to 4 syntaxes of cognitive conflict-based learning models, namely activation of preconceptions and misconceptions, presentation of cognitive conflicts, discovery of concepts and similarities, and reflection. Each syntax is designed to improve students' conceptual understanding and 4C skills. The results of the interactive multimedia prototype self-evaluation obtained very good criteria. The results of the prototype validity test obtained a very valid category. Interactive multimedia has been valid in material substance, learning design, visual communication display, and software utilization.